Espanol nivel 1 practicos/ejercicios - Mohd Sera'ai, Azlina; Lomoljo, Evangeline R. M. (Universiti Putra Malaysia Press, 2013)
Español Nivel1: Prácticos y Ejercicios is a workbook designed to help the beginner develop the basic language skills necessary to communicate in Spanish in most everyday situations. It is intended for any learner as a supplementary material to help him/her improve and master the basic grammatical structures of the language as well as vocabulary needed at this level, the lessons that are covered in the textbook being used. This exercise book contains a variety of drills and exercises that may help the learners build his/her grammar repertoire through constant practice for the authors believe in the popular saying that goes “Practice makes perfect”, that the more you practice, the better your skills are.